KINERJA KARYAWAN PERUSAHAAN UMUM DAMRI LAMPUNG - Romdoni, Panji Syahrul Romdoni; Finthariasari, Meilaty (UM. Bengkulu, 2025)
This research aims to determine the influence of perceived organizational support and employee engagement on employee performance at Damri Lampung Public Company, both partially and simultaneously. There are several independent variables (x) that will be discussed in this research, including Perceived Organizational Support and Employee Engagement of Damri Lampung Public Company Employees, which are the objects of the research, totaling 148 respondents. In this research, several data analysis techniques were used, including using instrument tests, classical assumption tests, analysis of respondent responses, multiple linear regression analysis, determinant coefficients, and also hypothesis testing. From the results of the multiple linear regression test, the regression equation obtained is as follows: 1. The research results show that the Perceived Organizational Support variable has a significant effect on Employee Performance at Damri Lampung Public Company 2. The research results show that the Employee Engagement variable has a significant effect on Employee Performance at Damri Lampung Public Company, 3. The results of the research show that the Perceived Organizational Support and Employee Engagement variables have a significant effect on Employee Performance at the Damri Lampung Public CompanyKeywords: Perceived Organizational Support, Employee Engagement, Employee Perfomance